Analysis of technology diffusion policies for renewable energy. The case of the Italian solar photovoltaic sector. (August 2021) - Bianco, Vincenzo; Cascetta, Furio; Nardini, Sergio
Abstract: The scope of the work is to depict a solid framework to interpret the capacity development of solar PV in Italy. To this aim the pivotal roles of public incentives is addressed and a vis a vis analysis of the regulatory framework and corresponding quantitative data is provided. The Italian regulatory framework did not provide an adequate focus on operational requirements for developing solar PV and allowed the speculative behavior of many investors. This is demonstrated by the correlation index between installed capacity and level of incentive equal to 0.988. Additionally, LCOE is calculated and from 2009 onward it is half of the average incentive level. Furthermore, the role of "followers" assumed by large power generators in the first phase of the PV development determined the absence of an industrial leadership. Oppositely, in a second phase, large utilities became more active on the PV market since they realized the impact on power market price. The linear correlation index between market price and PV capacity is found to be equal to −0.68, therefore price decreases at the increase of PV installed capacity and this is detrimental for large power utilities, thus they were pushed to be active in the PV sector.